Outcomes of repeat two-stage exchange hip arthroplasty for prosthetic joint infection. (June 2019) - Khan, N.; Parmar, D.; Ibrahim, M. S.; Kayani, B.; Haddad, F. S.
Abstract : Aims: The increasing infection burden after total hip arthroplasty (THA) has seen a rise in the use of two-stage exchange arthroplasty and the use of increasingly powerful antibiotics at the time of this procedure. As a result, there has been an increase in the number of failed two-stage revisions during the past decade. The aim of this study was to clarify the outcome of repeat two-stage revision THA following a failed two-stage exchange due to recurrent prosthetic joint infection (PJI). Patients and Methods: We identified 42 patients who underwent a two-stage revision THA having already undergone at least one previous two stage procedure for infection, between 2000 and 2015. There were 23 women and 19 men. Their mean age was 69.3 years (48 to 81). The outcome was analyzed at a minimum follow-up of two years. Results: A satisfactory control of infection and successful outcome was seen in 26 patients (57%). There therefore remained persistent symptoms that either required further surgery or chronic antibiotic suppression in 16 patients (38%). One-third of patients had died by the time of two years' follow-up. Conclusion: The rate of failure and complication rate of repeat two-stage exchange THA for PJI is high and new methods of treatment including host optimization, immunomodulation, longer periods between stages, and new and more powerful forms of antimicrobial treatment should be investigated. Cite this article: Bone Joint J 2019;101-B(6 Supple B):110–115.